Examining the Similarities between a Theocratic State and a Monarchical State through a Socio-political Lens - Gunawan, Nanda Permana; Muthmainah, Nida Ghoida; Ruslan, Ahmad (Ampera: A Research Journal on Politics and Islamic Civilization, 2024)
The objective of this study is to investigate the parallels between theocracy and monarchy from a socio-political perspective. Despite their distinct historical origins and sources of legitimacy, both forms of governance exhibit numerous similarities in their structural framework, leadership roles, legitimacy bases, and societal influences. Employing a socio-political approach, this research aims to explore how these systems impact societal dynamics, cultural values, and social structures. Initially, the study delves into the organizational structures of theocratic regimes and monarchies. It highlights the pivotal role of leaders as authoritative figures possessing ultimate executive authority. Examination of the presence of legislative bodies or advisory committees supporting decision-making processes reveals shared structural patterns across these governmental frameworks. Subsequently, the research scrutinizes the similarities in leadership roles and legitimacy sources. In monarchies, leaders often derive legitimacy from their royal lineage, whereas in theocracies, spiritual beliefs and religious credentials are instrumental in legitimizing rulership. Through this analysis, the study probes how both systems cultivate a socially acceptable perception of authority and legitimacy. Furthermore, the socio-political dimension of the research encompasses the impact on economic and social aspects of society. Leaders in theocratic and monarchical regimes significantly influence economic policies, wealth distribution, and social and cultural development. The study investigates how these policy decisions can contribute to economic disparities or shape the social and cultural fabric of society. Additionally, the research underscores the influence of theocratic and royal governments on cultural values and social norms. Leaders in both systems contribute to shaping societal perspectives on art, education, and social conventions. The study examines how leadership policies contribute to the formation of cultural identities and societal norms. Ultimately, this research aims to enhance understanding of the social and political dynamics within the contexts of theocracy and monarchy. By analyzing these similarities through a socio-political lens, the study seeks to elucidate the societal impacts of both governance models and identify potential implications for social and political progress.